Tax policy of Uzbekistan and its main directions (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article describes tax policy and its main directions in the conditions of economic reform, directions of tax policy development, tax policy aimed at optimizing tax benefits, current problems of tax policy modernization, and the procedure for ensuring financial stability of small business and private business entities.